MEASURING D? AND X ? IN THE HSX EDGE - Stephey, Laurie (My University, 2013)
Stellarator design has substantially improved over the past decade, but stellarator edge physics, especially in terms of heat and particle exhaust, is still not well-understood. Codes such as EMC3-EIRENE [8] are being used to model 3D edge physics, but these simulations must be informed by experimental measurements. Two important quantities that will be measured in the HSX edge are the perpendicular particle diffusivity, D?, and the perpendicular thermal diffusivity, ?. This work includes a comprehensive literature review, calculations that show that power deposition measurements are possible in HSX, preliminary diagnostic and experimental design ideas, and an outline for what will become a dissertation topic.